Cochrane Database of Systematic Reviews 2007
DOI: 10.1002/14651858.cd003868.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Oral morphine for cancer pain

Abstract: The randomised trial literature for morphine is small given the importance of this medicine. Most trials recruited fewer than 100 participants and did not provide appropriate data for meta-analysis. Trial design was frequently based on titration of morphine or comparator to achieve adequate analgesia, then crossing participants over in crossover design studies. It was not clear if these trials are sufficiently powered to detect any clinical differences between formulations or comparator drugs. Studies added to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(36 citation statements)
references
References 115 publications
0
33
0
1
Order By: Relevance
“…Morphine is considered the "gold standard" for relieving pain and is currently one of the most effective drugs available clinically for the management of moderate to severe pain associated with cancer. 1 Management of cancer pain may be important not only to the quality of the patients' lives but also to the cancer treatment itself. In the United States, 30 to 40% of newly diagnosed cancer patients and 90% of patients with advanced cancer report moderate to severe pain, which progresses in relation to tumor size, the degree of metastasis, the type of tumor, and its location.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Morphine is considered the "gold standard" for relieving pain and is currently one of the most effective drugs available clinically for the management of moderate to severe pain associated with cancer. 1 Management of cancer pain may be important not only to the quality of the patients' lives but also to the cancer treatment itself. In the United States, 30 to 40% of newly diagnosed cancer patients and 90% of patients with advanced cancer report moderate to severe pain, which progresses in relation to tumor size, the degree of metastasis, the type of tumor, and its location.…”
mentioning
confidence: 99%
“…The daily doses reported to produce analgesia range from 25 to 2000 mg morphine, with an average of between 100 and 250 mg in tolerant patients. 1 Dose titration is frequent with both instant-release and modified-release morphine products. Even though adverse effects occur, only 4% of patients discontinue treatment because of intolerable adverse effects.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Dette samsvarer med funnene i en Cochrane-oversikt om bruken av oral morfin mot kreftsmerte og i en norsk kunnskapsoppsummering (12,13). Imidlertid er det rapportert lavere prevalens av hallusinasjoner ved bruk av oksykodon sammenliknet med morfin for kreftsmerte (4,13).…”
Section: Kreftsmerteunclassified
“…Wiffen et al conducted a systematic review in order to assess the efficacy of oral morphine in relieving cancer pain, as well the incidence and severity of side effects (118). Forty five published randomized controlled studies (on 3061 subjects) were included in the meta-analysis, in which morphine was shown to be an effective analgesic for cancer pain.…”
Section: Opioid Analgesia For Cancer Painmentioning
confidence: 99%